Cannibalism and synchrony in seabird egg‐laying behavior. (8th August 2021) - Nurhan, Yosia I.; Henson, Shandelle M.
Abstract: During years of high sea surface temperature, food resources for glaucous‐winged gulls ( Larus glaucescens ) are scarce. In response, male gulls cannibalize the eggs of neighbors. When this occurs, female gulls in dense areas of the colony adopt a tactic of egg‐laying synchrony, in which they lay eggs synchronously on an every‐other‐day schedule. Field observations show that the first‐laid egg of each clutch is the most likely to be cannibalized. In this paper, we analyzed a discrete‐time model of egg‐laying behavior that tracks egg order in the nest. Using Jury conditions, we found that the equilibrium destabilizes into a two‐cycle as colony density (nests per unit area) increases through a critical value, and that the two‐cycle becomes increasingly synchronous as density increases further. We demonstrated that more eggs survive cannibalism in synchronous colonies than in nonsynchronous colonies. Recommendations for Resource Managers In colonial gulls, increased egg cannibalism and every‐other‐day egg‐laying synchrony are two behavioral consequences of rising sea surface temperature. As nest density (nests per unit area) increases, equilibrium egg laying destabilizes into increasingly synchronous two‐cycles. More eggs survive cannibalism in synchronous colonies than in nonsynchronous colonies.